AN ANALYSIS OF INTERROGATIVE EXPRESSIONS IN THE SHORT STORY 'MAHFAZHAH' FROM THE COLLECTION 'ISN’T THAT SO?' BY YUSUF IDRIS: A SEMIOTIC STUDY BASED ON MICHAEL RIFFATERRE'S THEORY: TAḤLĪL AL-ISTIFHĀM FĪ AL-QIṢṢAH AL-QAṢĪRAH "MAḤFAẒAH" MIN AL-MAJMŪ‘AH AL-QIṢAṢIYYAH "A-LAYSA KA-DHĀLIK" LI-YŪSUF IDRĪS (DIRĀSAH SĪMĀ’IYYAH BI-MANHAJ MICHAEL RIFFATERRE) - Riza, Ali; Munir, Dede Rizal (Journal of Arabic Language and Literature (ALLAIS), 2025)
This study aims to explore the function and semantic role of interrogative expressions in Yusuf Idris’s short story Mahfazhah, through the lens of Michael Riffaterre’s semiotic theory. The research investigates how these linguistic tools shift from simple interrogatives into rhetorical devices that convey psychological, social, and philosophical dimensions, thereby deepening textual interpretation and revealing hidden meanings. A qualitative descriptive method is employed, specifically content analysis. Interrogative sentences are extracted and categorized according to their types, then analyzed using Riffaterre’s semiotic concepts to uncover the subtextual meanings embedded within the narrative structure and cultural context. The findings reveal that interrogatives such as “mā” and “limādhā” reflect internal confusion; “hal” and the hamzah interrogative express existential alienation; “kayfa” and “ayna” portray economic hardship; while “man” and “ayy” articulate identity struggles and individual-society tension. Thus, interrogatives in the text become central rhetorical elements charged with symbolic and interpretive depth. This research contributes to the applied understanding of Riffaterre’s semiotics and offers an analytical model for interpreting short stories through a semiotic perspective. It supports scholars and students of Arabic literature in uncovering deeper textual meanings within a rigorous scientific framework.